Facile preparation of high-performance spinel LiMn2-xCuxO4 cathodes by microwave-induced solution flameless combustion. (May 2021) - Chen, Ruifang; Wen, Bixia; Li, Hong; Xiang, Mingwu; Su, Changwei; Guo, Junming; Bai, Wei; Sa, Zhaoyao
Abstract: A series of LiMn2-x Cux O4 (0 ≤ x ≤ 0.1) cathode materials were synthesized via a rapid microwave-induced solution flameless combustion technique, and the structure, morphology and electrochemical performances of the LiMn2-x Cux O4 samples were investigated in detail. All the as-prepared samples are the single crystal materials with a high crystallinity and correspond to the well-defined spinel structure. The spinel structure stability is effectively improved by the appropriate Cu-doping that is conducive to increasing the average valence of Mn and reducing lattice parameter. Consequently, the optimized LiMn1.925 Cu0.075 O4 sample delivers a first discharge specific capacity of 108.5 mAh g −1 at 1 C and achieves the long-term charge/discharge cycle of 1000 cycles. At high current rate of 5 C and 10 C after 1000 cycles, the capacity retention of over 61% can be maintained. Even at the elevated temperature of 55 °C, the high initial capacity of 111.4 mAh g −1 and capacity retention of 63.91% are also delivered after 100 cycles at 1 C. This is ascribed to the favorable Li + diffusion kinetics, low charge transfer resistance and apparent activation energy. Highlights: Cu-doped LiMn2 O4 is rapidly synthesized via a microwave-induced solution combustion. Cu-doping improves average Mn valence and stabilizes spinel structure. Single crystal LiMn1.925 Cu0.075 O4 shows long cycle stability and good rate capability.